A new Helsinki for the OSCE? Chances for a revival of the European security dialogue - Solveig Richter; Wolfgang Zellner (Stiftung Wissenschaft und Politik (SWP), 2008)
The five-day war in Georgia has exposed an apparent crisis in the approach to co-operative security in Europe. The European Union and NATO have found it difficult to deal with this crisis and are increasingly in disagreement with the key actor, Russia. Against this background, a succession of politicians have brought the OSCE into play again. Recently, in Evian, Nicholas Sarkozy, on behalf of the EU Presidency, suggested an OSCE Summit in 2009 and found Russian President Dmitry Medvedev open to the idea. The chances of success for this approach can, for all intents and purposes, be viewed sceptically. After all, in recent years, the OSCE itself has been a source of dispute between Russia and the Western states. However, the OSCE today offers the only remaining institutional framework capable of reviving the European security dialogue. With key topics such as the settlement of regional conflicts at issue, important progress can be achieved at the OSCE Ministerial Council meeting in Helsinki, provided that the political will is there
Keywords: 320